Aqueous photocatalytic oxidation of lignin and humic acids with supported TiO2 - Elina Portjanskaja; Sergei Preis; Juha Kallas (International Journal of Photoenergy)
The photocatalytic oxidation (PCO) of UV-irradiated aqueous solutions containing humic acids and lignin was studied. The photocatalyst TiO2 was attached to buoyant hollow glass microspheres and glass plates. A maximum oxidation efficiency as low as 1.1 and 2.54 mg W−1h−1 for humic acids and lignin, respectively, was achieved in neutral and alkaline media with 25 gm−2 of the buoyant catalyst. In acidic media, efficiency was even lower. The photocatalytic efficiency with the photocatalyst attached to glass plates was about 3 to 4 times higher than that for the buoyant catalyst. Ferrous ions added to acidic solutions did not increase the rate of PCO of humic acids. However the addition of Fe2+ ions, up to 0.05 mM, to the lignin solution leads to a dramatic increase, about 25%, in PCO efficiency. A further increase in ferrous ion concentration results in a decrease in the PCO efficiency of lignin. Proceeding most likely by a radical mechanism, the efficiency of PCO of humic acids did not benefit from an excessive presence of hydroxyl radical promoters, such as hydrogen peroxide, although the reaction rate increased. However, PCO of lignin in the acidic medium, where OH.-radical formation is suppressed, benefited from the introduction of hydrogen peroxide due to promoted radical formation.